Efficient pricing of large value interbank payment systems - Cornelia Holthausen; Jean-Charles Rochet (European Central Bank (ECB), 2002)
This paper studies the efficient pricing of large-value payment systems in the presence of unobservable heterogeneity about banks' future payment volumes. It is shown that the optimal pricing scheme for a public monopoly system involves quantity discounts in the form of a decreasing marginal fee. This is also true when the public system competes with a provate system characterized by a lower marginal cost. However in this case, optimal marginal fees in the public system are lower than its marginal cost, and fixed fees have to be levied. We also study the case of competition between several public systems. The structure of the optimal tariff depends on the willigness of Central Banks to allow by-pass.
Keywords: G28; E58; D42; D43; 330; mixed duopoly; non-linear pricing; payment systems; public monopoly